Ina Batzke, Eric C. Erbacher, Linda M. Hess, and Corinna Lenhardt, eds. Exploring the Fantastic: Genre, Ideology, and Popular Culture. Transcript Verlag, 2018. - Annabelle Dolidon (Studies in 20th & 21st Century Literature, 2019)
Review of Ina Batzke, Eric C. Erbacher, Linda M. Hess, and Corinna Lenhardt, eds. Exploring the Fantastic: Genre, Ideology, and Popular Culture. Transcript Verlag, 2018. 294 pp.
Keywords: Fantastic